A Potential Diabetic-Friendly Food Material: Optimization, Nutritional Quality, Structural Characteristics, and Functional Properties of Oat and Purple Potato Fermented by Ganoderma lucidum Mycelium - Yingxian Guan; Tong Zhao; Anrong Zhang; Di Zhang; Xiaoxiao Huang; Xiao Fang; Jiajun Geng; Jie Gang (Fermentation)
Dietary intervention is the basis for the treatment of diabetes mellitus. This study employed Ganoderma lucidum (GL) mycelium to ferment a compound medium of oat and purple potato (OPP), optimized fermentation conditions to increase the triterpene content in the resulting product (F-OPPF), and systematically investigated the impact of fermentation on the nutritional quality, structural characteristics, and functional properties of OPP. The results indicated that the triterpene content in F-OPPF significantly increased from 8.53 mg/g to 17.23 mg/g under optimal conditions (temperature: 28 °C, inoculum size: 10%, material quantity: 36 g/250 mL, and fermentation time: day 13). Fermentation resulted in enhanced nutritional quality, with increased contents of protein, soluble protein, crude fiber, ash, mineral elements, essential amino acids, polysaccharides, flavonoids, and total phenols. Mycelium not only enveloped the OPP surface but also penetrated its interior, forming a porous honeycomb-like structure. The types of reactive groups and crystals (C + V-type) were not changed after fermentation, while the crystallinity increased. F-OPPF exhibited positive changes in thermogravimetric properties, antioxidant and hypoglycemic activities, and adsorption capacity of insoluble dietary fiber. Additionally, incorporating F-OPPF into the diet markedly reduced fasting blood glucose levels and promoted weight gain in T2DM rats induced by a high-fat diet and streptozotocin. The fermented groups exhibited improvements in glyco- and lipo-metabolism, oxidative stress, and the function and pathological morphology of the pancreas, liver, and kidneys compared to the unfermented group. Collectively, these findings suggested that GL mycelium fermentation enhanced the nutritional and functional values of OPP, and F-OPPF holds potential as a raw material for developing diabetic-friendly foods.